Usefulness of Diffusion-Weighted MRI for Differentiation between Parkinson’s Disease and Parkinson Variant of Multiple System Atrophy - Eun Joo Chung; Eung Gyu Kim; Jong Seok Bae; Choong Ki Eun; Kwang Sig Lee; Minkyung Oh; Sang Jin Kim (Journal of Movement Disorders, 2009)
Background and Purpose: Several studies have reported that diffusion-weighted imaging (DWI) is able to help discriminate a Parkinson variant of multiple system atrophy (MSA-p) from Parkinson’s disease (PD) on the basis of the increased regional apparent diffusion coefficient (rADC). We analyzed the usefulness of DWI by using the rADC for differential diagnosis between MSA-p and PD and investigated the correlation between the rADC value and clinical features of MSA-p and PD. Methods: Twelve patients with PD and 10 with MSA-p were studied. The rADC value was determined in different brain regions, including the dorsal putamen (DP) and middle cerebellar peduncles (MCP). Results: The rADC values of the DP showed a greater increase in MSA-p patients than in PD patients (p=0.03). MSA-p patients also presented increased rADC values of the MCP compared with PD patients (p=0.0001). In particular, the sensitivity, specificity and positive predictive values of the MCP rADC were higher than those of the DP rADC. However, DP and MCP rADC values were not correlated with clinical features in either MSA or PD patients. Conclusions: DWI discriminated between PD and MSA-p based on rADC values in DP and MCP. The MCP rADC value, in particular, could better discriminate MSA-p from PD.